2015
DOI: 10.1021/acschemneuro.5b00032
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Prevents Neuroinflammation in Chronic Constriction Injury Rats through Nuclear NFκB Downregulation in the Dorsal Root Ganglion and Spinal Cord

Abstract: Atorvastatin, traditionally used to treat hyperlipidemia, belongs to a class of 3-hydroxy-3-methyl-glutaryl coenzyme A (HMG-CoA) reductase inhibitors. This study investigated the antineuroinflammatory and antihyperalgesic effects of atorvastatin in dorsal root ganglia (DRG) and spinal cord for chronic constriction injury (CCI) neuropathic pain in rats. Fifty-four Sprague-Dawley rats were divided into three groups including sham, CCI, and CCI+atorvastatin. Rats were orally administered atorvastatin (10 mg/kg/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 61 publications
(110 reference statements)
0
32
0
Order By: Relevance
“…Activated spinal glia were observed after oxaliplatin injection, and intrathecal injection of minocycline and fluorocitrate, which decrease the activation of astrocytes and microglia respectively, effectively attenuated neuropathic pain [22]. Activated glia are known to contribute to neuropathic pain by releasing pro-inflammatory cytokines such as IL-1β and TNF-α [1315], and suppressing the activation of astrocytes and microglia down-regulated the expression of pro-inflammatory cytokines, which led to the alleviation of nerve injury-induced neuropathic pain [40, 41]. Intrathecal injection of pro-inflammatory cytokines such as IL-1β and TNF-α evoked hyperalgesia and allodynia in naive animals [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Activated spinal glia were observed after oxaliplatin injection, and intrathecal injection of minocycline and fluorocitrate, which decrease the activation of astrocytes and microglia respectively, effectively attenuated neuropathic pain [22]. Activated glia are known to contribute to neuropathic pain by releasing pro-inflammatory cytokines such as IL-1β and TNF-α [1315], and suppressing the activation of astrocytes and microglia down-regulated the expression of pro-inflammatory cytokines, which led to the alleviation of nerve injury-induced neuropathic pain [40, 41]. Intrathecal injection of pro-inflammatory cytokines such as IL-1β and TNF-α evoked hyperalgesia and allodynia in naive animals [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“… 13 15 Activation of NF-κB participated in nerve injury or inflammation-induced pathological pain. 16 , 17 Recent studies showed that NF-κB is also involved in chemotherapy-induced chronic pain. 8 , 9 However, whether activation of NF-κB p65 in DRG is involved in oxaliplatin-induced chronic pain is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory reactions are the primary cause of sequential damage associated with SCI, and inflammation is an important part of the acute SCI pathophysiological mechanism (24). SCI promotes a series of molecular biological events which lead to inflammatory cell activation, arising from circulatory system infiltration in spinal cord tissue, pro-inflammatory factors and neurotoxin release, and the generation of oxygen free radical and nitroso compounds which lead to cellular lesions (25). In the present study, it was demonstrated that sparstolonin B significantly decreased IL-18, IL-6, IL-1β, and IL-23 levels, and TNF-α and IFN-γ levels, in SCI rats.…”
Section: Discussionmentioning
confidence: 99%